The Role of Endurance in Cricket Player Performance - Juniarto, Mastri (Gladi : Jurnal Ilmu Keolahragaan, 2026)
Cricket is an intermittent sport that requires the ability to maintain physical and technical performance over long match durations. This study aims to measure and analyze the role of endurance on playing performance in 18 athletes from the Jakarta Men’s Cricket Training Center. Cardiovascular endurance was estimated using the Bleep Test (Multistage Fitness Test) to obtain VO₂max values, while field performance was observed in three main aspects: running, bowling, and fielding. The results showed VO₂max in the range of 34.8–49.5 ml/kg/min with a mean of 42.5 ± 3.97 ml/kg/min and a range of 14.7. The majority of athletes (±60%) were in the good category (41–46 ml/kg/min), two athletes reached the very good category (>49 ml/kg/min), and three athletes were in the poor category (<38 ml/kg/min). Descriptively, athletes with higher VO₂max tend to demonstrate more consistent fielding performance, particularly in running efficiency, bowling accuracy, and fielding response, while athletes with lower VO₂max are more susceptible to performance decline as fatigue increases. These findings emphasize the importance of strengthening aerobic endurance as a fitness base to support consistent cricket performance. Implementation of interval/circuit-based conditioning programs and regular monitoring is recommended to reduce fitness variation among athletes